(Self-)selection and expertise among decision-makers in the European Parliament. Issue 1 (2nd January 2018) - Hermansen, Silje Synnøve Lyder
ABSTRACT: Rapporteurs in the European Parliament (EP) are the most influential members in terms of the legislation they handle. They are appointed by their political groups. In making these appointments, these groups need to accommodate both their collective needs and individual requests. This article explores situations in which the collective need for information is prioritised: the codecision procedure. The data includes allocations over a 10-year period (2004–2014) in three of the most powerful EP committees, as well as key career choices among members. EP groups emphasise policy-specific knowledge. They also pay attention to individual members' requests for exposure, but only when the expected policy drift is minimal. Harsh selection during the allocation of codecision reports creates pressure to accommodate a greater selection of legislators during other attractive report allocations. Own-initiative reports therefore affect allocation of codecision reports negatively.